2011
DOI: 10.1002/fuce.201000020
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Optimisation of the Oxide Ion Conductivities of Apatite‐Type Germanates

Abstract: Recently, apatite‐type germanates La9.33+xGe6O26+3x/2 have attracted considerable interest due to their high oxide ion conductivities. Research has shown that the key defects are oxide ion interstitials which lead to the conversion of some of the GeO4 units to GeO5. Consequently there has been a large interest in the preparation of high oxygen excess samples with high defect concentration. This strategy, however, leads to a reduction in symmetry from hexagonal to triclinic for x > 0.4, and consequently to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…This anomaly clearly needs more study, although it is suggested that it may be related to interstitial defect trapping by the dopant leading to the formation of MO 5 units and consequent local relief of lattice strain by the dopant. The Raman studies, reported here, show clear evidence for this defect trapping in the case of W, while such defect trapping has also been inferred from conductivity studies for the series La 10 Ge 6-x Ti x O 27 [44].…”
Section: Resultssupporting
confidence: 79%
“…This anomaly clearly needs more study, although it is suggested that it may be related to interstitial defect trapping by the dopant leading to the formation of MO 5 units and consequent local relief of lattice strain by the dopant. The Raman studies, reported here, show clear evidence for this defect trapping in the case of W, while such defect trapping has also been inferred from conductivity studies for the series La 10 Ge 6-x Ti x O 27 [44].…”
Section: Resultssupporting
confidence: 79%
“…16) The electrical conductivity of the La 9.5 Ge 5.7 Ga 0.3 O 26.1 ceramic sintered at 1450°C, with respect to temperature, appeared to be lower than that of an 8YSZ ceramic 16) at a temperature below 700°C. As the temperature rose above 700°C, the former displayed higher electrical conductivity values than the latter, which reached 4.02 © 10 ¹2 Scm ¹1 at 800°C.…”
Section: )mentioning
confidence: 98%
“…16 2) Different from the major ion conduction mechanism in fluorite-or perovskite-type materials closely relating to oxygen vacancy, it is thought that the conduction of the apatite materials occurs via interstitial oxide ions. The hexagonal structure is composed of isolated MO 4 tetrahedra-forming channels running parallel to the c-axis, with A cations located in two cavity sites, one 7 coordinate and one 9 coordinate, where the loosely bounded oxideconducting anions are located.…”
Section: Introductionmentioning
confidence: 99%
“…For the selection of the compounds and the crystal symmetry (space group) of the compounds the literature references are Shannon and Prewitt (1976), Rabe et al (1992), Leon-Reina et al (2003, Sansom et al (2005), Kendrick and Slater (2008aÀc), Pramana et al (2008), and Orera et al (2011). The input data for each compound was the following: • At each of three sites (Lanthanum, Germanium, and Oxygen), a quantitative measurement of each of four properties (Zunger's Pseudopotential Core Radii Sum, MartynovÀBatsanov Electronegativity, Valence Electron Number, and Shannon's Ionic Radius) for a total of 11 measurements per compound (one property, Shannon's Ionic Radius, did not apply at the Oxygen site).…”
Section: Materials Science Proof Of Concept Modelmentioning
confidence: 99%